The Relationship between School Connectedness and Academic Engagement: Mediating Role of Mindfulness - Rouhollah Aghasaleh; Saba Rasouli Amlashi; S. Abdolvahab Samavi (Iranian Journal of Educational Research)
Objective: One of the burgeoning areas of interest within the realm of education pertains to student engagement, a central component of positive psychology (PP). Another fundamental concept in the PP literature is school connectedness, which underscores the belief students hold regarding the care shown by adults and peers in the educational environment towards their academic progress and personal welfare. Additionally, mindfulness, a pivotal term in the field of PP, offers noteworthy advantages such as enhancing working memory and reducing stress levels, consequently fostering academic involvement. Given the significance of school connectedness and mindfulness in academic engagement, the present study endeavors to examine the association between school connectedness and academic engagement in high school students, with mindfulness serving as a mediator. Methods: A total of 300 high school students from Bandar Abbas participated in the study, responding to scales measuring mindfulness, school connectedness, and academic engagement. Subsequently, structural equation modeling was employed to illuminate potential relationships. Results: The results indicated a significant correlation between school connectedness and academic engagement. Furthermore, the findings demonstrated that both school connectedness and mindfulness serve as positive and significant predictors of academic engagement. Moreover, the results substantiated the mediating role of mindfulness. Conclusions: These findings offer valuable insights for educators in enhancing classroom practices.